Hemorrhagic Meckel's diverticulum in an older woman diagnosed by repeated angiographies - Jee Suk LEE,; Won Moon,; Seun Ja PARK,; Moo In PARK,; Kyu Jong KIM,; Sang Ho LEE,; Hee Kyung Chang,; Gyu Sik JUNG, (Turkish Journal of Gastroenterology, 2019)
-